Recovery of volatile fatty acids via membrane contactor using flat membranes: Experimental and theoretical analysis - TUĞTAŞ KARNABAT, ADİLE EVREN (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
Volatile fatty acid (VFA) separation from synthetic VFA solutions and leachate was investigated via the use of a membrane contactor. NaOH was used as a stripping solution to provide constant concentration gradient of VFAs in both sides of a membrane. Mass flux (12.23 g/m(2) h) and selectivity (1.599) observed for acetic acid were significantly higher than those reported in the literature and were observed at feed pH of 3.0, flow rate of 31.5 +/- 0.9 mL/min, and stripping solution concentration of 1.0 N. This study revealed that the flow rate, stripping solution strength, and feed pH affect the mass transfer of VFAs through the PTFE membrane. Acetic and propionic acid separation performances observed in the present study provided a cost effective and environmental alternative due to elimination of the use of extractants. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Gas membrane; Leachate; PTFE; Separation; Volatile fatty acids; ANAEROBIC-DIGESTION; ACETIC-ACID; PERVAPORATION MEMBRANES; FERMENTATION BROTH; AMMONIA REMOVAL; SEPARATION; EXTRACTANTS; WASTEWATERS; INHIBITION; WASTE